THE EFFECT OF PRODUCTS, PROMOTION AND DISTRIBUTION ON PURCHASING DECISIONS OF SCARLETT COSMETICS (A SURVEY OF RETAIL STORES IN BANGKINANG KOTA) - Ulfah Rahmadani; Muhammad Yusril; Arman Arman (STIE Bangkinang Publishing, 2022)
This study aims to determine the effect of product, promotion and distribution on purchasing decisions of Scarlett cosmetics (a survey of retail stores in Bangkinang Kota). The types and data sourcesu used in this study are primary and secondary data, while the data collection technique is using questionnaires, research files, observations. in this study, the researcher used multiple linear analysis with a sample of 100 people as the data analysis. The sample collection technique is using accidental sampling technique. Based on the results of the simultaneous variables test, product, promotion and distribution have an effect on for Scarlett cosmetics purchasing decisions (a survey of retail stores in Bangkinang Kota), while based on a partial variables test, product, promotion and distribution have shown to have a significant effect individually on Scarlett cosmetic purchasing decisions (survey on retail stores in Bangkinang Kota), The closeness relationship occurs between product variable, promotion and distribution on purchasing decisions is very strong Meanwhile, the independent variable contributions to the dependent variable is 59.9%,.